Pelatihan Desain Aplikasi Modern Untuk Pembelajaran Pembuatan Prototipe Interaktif Menggunakan Figma Di Pondok Pesantren Assaadah - Jupron; Rilo Pambudi; Ibnu Haris Agam; Obit Zunanda; Achmad Rizkyanto; Muhamad Jusub; Aditya Purna; Satia Adi Irawan; Kasna Imanuel; Nurul Akbar; Abdul; Rahman Harahap (CV. Multi Kreasi Media, 2024)
The training on modern application design for learning the creation of interactive prototypes using Figma at Pondok Pesantren Assa'adah aims to provide knowledge and practical skills in designing and developing interactive digital applications. Figma, as a cloud-based design tool, allows participants to create prototypes that can be tested directly with users without the need for deep coding skills. In this training, participants will be introduced to the basic concepts of user interface (UI) and user experience (UX) design, as well as the process of creating prototypes that can be tested and refined. By integrating modern design technology, this training is expected to enhance the students' ability to innovate and create digital applications that can be used for various educational and social needs within the Pondok Pesantren environment. Through this training, participants will gain hands-on experience in utilizing Figma to produce effective, creative, and implementable interactive prototypes.